ACCESS TO HEALTH CARE FOR WOMEN AS HEAD OF THE FAMILY IN POOR HOUSEHOLDS: CASE STUDY OF HEALTH CARE FOR NATIONAL HEALTH INSURANCE PROGRAM IN INDONESIA - Veronica Veronica; Krisna Puji Rahmayanti (Andalas University, Faculty of Public Health, 2019)
This study aims to analyze the access of women as head of the family in poor households in national health insurance (JKN KIS) in Indonesia. Currently, there are still many problems related to JKN KIS effectiveness due to many cases show that many obstacles and difficulties occurred in the implementation stage. This problem increases the vulnerability of the poor household especially household with women as the head of the family. Therefore, this study conduct survey in Kapuk Village, Cengkareng Sub District, Jakarta Barat District, Jakarta Province as Jakarta is the barometer of public service access in Indonesia as developing country; this village has the highest number of women as head of the family; and Jakarta Barat District is the second highest poverty level in the province. This study uses the quantitative approach with mix method data collection using in-depth interviews and survey. This study uses "five-dimensional access theory" which includes availability, accessibility, affordability, adequacy, and acceptability. The result of the study found that all accessibility dimension are fulfilled except the affordability dimension. The affordability dimension proves that even though national health insurance gives financial assistance for the poor households to get health care through JKN KIS, poor families have difficulty in fulfilling additional financial losses due to public services such as the cost for transportation cost and time loss.   Keywords: Health Care Access; National Health Insurance Program; Women; Poor Households